0
$\begingroup$

By method of variation of parameters find the PI of the differential equation $$\frac{dy}{dx}+2y=4e^{2x}$$ I have learned how to do the find out the PI of second order differential equation. But, here is first order. I can't find any solution of this. Please help me. $$\text{I tried to use the Wronskian method like:}$$ $$Let, y=e^{mx}\\ \implies Dy=me^{mx}$$ $$\text{Then, the auxiliary equation is:}\\ m+2=0\\ \implies m=-2$$ $$Then, C.F.=c_1e^{mx}$$ $$P.I. y_p= u(x)e^{mx}$$ Then, there we had to find wronskian. But, I can't get it how to find that...

$\endgroup$
  • $\begingroup$ Please show your work, if you're able to do for the second order then what's wrong with first order ? $\endgroup$ – Siddhartha Apr 26 at 3:38
  • $\begingroup$ looking at the right side, you could use the Ansatz $y=Ae^{2x}$ $\endgroup$ – J. W. Tanner Apr 26 at 3:42
2
$\begingroup$

You don't need the Wronskian here it's a first order DE $$\frac{dy}{dx}+2y=4e^{2x}$$ Solve the homogeneous equation $$\frac{dy}{dx}+2y=0$$ $$\ln y =-2\int dx=-2x+c$$ $$y=ce^{-2x}$$ Variation of parameter needs $$y=c(x)e^{-2x}$$ $$y'=c'(x)e^{-2x}-2e^{-2x}c(x)$$ Plug this in the differential equation and solve for $c(x)$. $$y'+2y=4e^{2x}$$ $$c'(x)e^{-2x}-2e^{-2x}c(x)+2c(x)e^{-2x}=4e^{2x}$$ Can you take it from here ?

| cite | improve this answer | |
$\endgroup$
  • 1
    $\begingroup$ Yes, I got it. Thanks a lot🥳 $\endgroup$ – Ankita Pal Apr 26 at 4:20
  • $\begingroup$ You 're welcome @AnkitaPal $\endgroup$ – Aryadeva Apr 26 at 4:20
2
$\begingroup$

Consider a general scalar dynamical system where $a,b \in \mathbb{R}$ $$\dot{x}(t)=ax(t)+bu(t) \implies \dot{x}(t)-ax(t)=u(t)$$ Now multiply both sides by $e^{-at}$, you get $$e^{-at} \left( \dot{x}(t)-ax(t)\right)=\frac{\mathrm{d}}{\mathrm{d}t}e^{-at}x(t)=e^{-at}bu(t)$$Now integrating this between $0$ to $t$ gives you $$x(t)=e^{at}x(0)+e^{at}\int_0^t e^{-as}b u(s)\mathrm{d}s$$ Where the first term is the response due to initial condition $x(0)$ and the second term is the forced response due to the input $u(t)$

| cite | improve this answer | |
$\endgroup$
  • 1
    $\begingroup$ Thanks for the clue $\endgroup$ – Ankita Pal Apr 26 at 4:26

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.